Short-term plyometric jump training improves repeated-sprint ability in prepuberal male soccer players - Negra, Y.; Chaabene, H.; Fernandez-Fernandez, J.; Sammoud, S.; Bouguezzi, R.; Prieske, O.; Granacher, U. (The Journal of Strength and Conditioning Research, 2020)
This study examined the effects of a short-term (i.e., 8 weeks) combined horizontal and vertical plyometric jump training (PJT) program in combination with regular soccer-specific training as compared with soccer-specific training only on jump and change of direction (CoD) performances, speed, and repeated-sprint ability (RSA) in prepuberal male soccer players. Twenty-four players were recruited and randomly assigned to either a PJT group (PJTG; n = 13; 12.7 ± 0.2 years) or an active control group (CONG; n = 11; 12.7 ± 0.2 years). The outcome measures included tests for the assessment of jump performance (drop jump from 20- to 40-cm height [DJ20 and DJ40] and 3-hop test [THT]), speed (20-m sprint), CoD (T-test), and RSA (20-m repeated shuttle sprint). Data were analyzed using magnitude-based inferences. Within-group analyses revealed large performance improvements in the T-test (d = -1.2), DJ20 (d = 3.7), DJ40 (d = 3.6), THT (d = 0.6), and the RSAtotal (d = -1.6) in the PJTG. Between-group analyses showed greater performance improvements in the T-test (d = -2.9), 20-m sprint time (d = -2.0), DJ20 (d = 2.4), DJ40 (d = 2.0), THT (d = 1.9), RSAbest (d = -1.9), and the RSAtotal (d = -1.9) in the PJTG compared with CONG. Eight weeks of an in-season PJT in addition to regular soccer-specific training induced larger increases in measures of physical fitness in prepuberal male soccer players compared with regular soccer-specific training only. More specifically, PJT was effective in improving RSA performance.